New Paradigm in Abilitation of Premature Children with Perinatal Pathology — Therapeutic Stages Personalization: Cohort Study - Alexander A. Baranov; Leyla S. Namazova-Baranova; Irina A. Belyaeva; Tatiana V. Turti; Alexey A. Vishneva; Alexey I. Molodchenkov (Вопросы современной педиатрии, 2020)
Background. The abilitation of premature infants acquires importance due to the increased prevalence of delayed health disorders in these children. The article considers the issues of individualization of rehabilitation treatment for premature infants according to prediction of perinatal pathology outcomes, determining the individual levels of «abilitation windows» and developing personalized abilitation programs.Objective. The aim of the study was to determine individual timely sensitive ontogenesis stages («abilitation windows») for premature children with various perinatal pathology, as well as the most effective methods of rehabilitation treatment according to the maturity of the child and the type of neurosomatic deficiency.Methods. Two-stage cohort study of premature children with gestational age of 250–6–300–6 weeks was conducted. Stage 1 — retrospective analysis of «abilitation windows» in 115 premature children, development of prognostic scenarios. Stage 2 — prospective cohort study of 109 premature children, using abilitation methods in this cohort according to predicted events and estimation of abilitation efficacy. Medical interventions: familyoriented educational counseling, kinesiotherapy, physiotherapy, neuroprotectors, music therapy.Results. Information matrixes on filling ontogenetic abilitation periods have been developed, as well as age limits for «abilitation windows» have been defined on the 1st stage. Sensitive interval has been established for the use of stimulating effects in extremely immature children (postconceptional age of 34–37 weeks). The leading role of abilitation protective measures has been identified. Perinatal pathology outcomes have been analyzed in children from retrospective analysis group. Direct abilitation of premature children (from birth to 18 months) was carried out on the 2nd stage of the study according to probability forecasts. The priority of non-drug abilitation methods usage in immature children was confirmed. The need in step-by-step dynamic correction of abilitation programs was established.Conclusion. Prognostic significance of perinatal period events and individual postconceptional age in «abilitation windows» development for premature children was determined. The priority of non-drug abilitation for such patients (including family-oriented pedagogics) is established.